2011
DOI: 10.1111/j.1447-0756.2011.01707.x
|View full text |Cite
|
Sign up to set email alerts
|

Fetal heart rate parameters and perinatal outcomes in fetuses with nuchal cords

Abstract: Computerized analysis of FHR would be helpful to assess fetal status, especially in cases of multiple NCs. Multiple NCs may be a subliminal risk factor for the babies even though they present no complications at delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
1
6
0
1
Order By: Relevance
“…We also observed that neonates whose mothers exhibited NFHT had 28.9% greater risk of having nuchal cord, RR Z 1.289, 95% CI (1.185, 1.402) than neonates whose 15 reported that fetal heart rate variability was lower in fetuses with nuchal cord compared to those without and it continued to decrease with multiple nuchal cords. However, this did not result in any adverse neonatal outcome.…”
Section: Discussionsupporting
confidence: 51%
“…We also observed that neonates whose mothers exhibited NFHT had 28.9% greater risk of having nuchal cord, RR Z 1.289, 95% CI (1.185, 1.402) than neonates whose 15 reported that fetal heart rate variability was lower in fetuses with nuchal cord compared to those without and it continued to decrease with multiple nuchal cords. However, this did not result in any adverse neonatal outcome.…”
Section: Discussionsupporting
confidence: 51%
“…33 A healthy newborn was delivered by Cesarean at 33 and 1/7 weeks' gestation with the presence of a true knot confirmed at delivery. 32 In contrast to single nuchal cords, which occur in between 15.8% and 30% of singleton fetuses at term, and have not been unequivocally associated with significant adverse perinatal outcome, 6,20,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] true knot(s) of the umbilical cord occur in 0.04% to 3% of deliveries, and have been associated with perinatal morbidity in 11% of cases, and a notable 4 to10 fold increase in stillbirth. 28,29,[53][54][55][56][57][58][59][60][61][62] Although (multiple) true knots of the umbilical cord have been infrequently implicated with fetal growth restriction, a causal association remains unproven.…”
Section: True Knot(s) Of the Umbilical Cordmentioning
confidence: 99%
“…85 Hoh et al in 2012, in data regarding 150 cases with nuchal cords (300 cases without nuchal cords, 124 cases of single nuchal cord, and 26 with multiple nuchal cords), noted that the birth weight of infants with multiple nuchal cords was significantly lower than that of infants without nuchal cords (3317±24 grams versus 3054±55 grams, P=0.0008). 86 Similarly, we followed a patient with a persistent quadruple nuchal cord throughout the third trimester (Figure 4). 87 Repeat sonographic evaluations at 2-week intervals demonstrated gradual continued decelerating fetal growth.…”
Section: Fetal Growthmentioning
confidence: 99%